A Proposed Comprehensive Novel Model (CN-Model): To Drive Continuous Quality Improvement (CQI) on Engineering Programme in Institution of Higher Learning - Ching Yee Yong,; Samat Iderus, (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2024)
The Continuous Quality Improvement (CQI) model is an evaluative tool for academic performance in teaching and learning (T&L), emphasizing student enablement and continuity. Recognizing the inherent subjectivity in T&L performance assessment, the evaluation process is complex and intricate. In pursuit of an enhanced T&L experience, a novel model was introduced and rigorously tested across four consecutive semesters within the Electrical Engineering Programme at a University. The study encompassed 90 courses spanning from year 1 to year 4, involving 1062 students. Qualitative and quantitative parameters were considered, including student failure rates and strategic plans. The results demonstrated a significant and consistent reduction in the failure rate each semester. This comprehensive model not only contributes to professional development within the T&L Malaysian Qualifications Framework (MQF) Level 6 sector but also exhibits potential applicability in diverse performance evaluation contexts.